2019
DOI: 10.1016/j.jpeds.2018.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Children and Young Adults with Marfan Syndrome

Abstract: Objective To assess health-related quality of life (HRQOL) in a large multicenter cohort of children and young adults with Marfan syndrome (MFS) participating in the Pediatric Heart Network Marfan Trial. Study design The Pediatric Quality of Life Inventory (PedsQL) 4.0 Generic Core Scales were administered to 321 subjects with MFS (5–25 years). PedsQL scores were compared with healthy population norms. The impact of treatment arm (atenolol versus losartan), severity of clinical features, and number of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 39 publications
7
59
0
Order By: Relevance
“…None of the three studies found that medical severity of MFS were associated to decreased QoL. The largest study found that the patients‐reported symptoms and neurodevelopmental disorders were associated to lower QoL. This study claim that symptoms such as pain, fatigue, psychosocial distress and learning disability may have greater impact on QoL than the objective biomedical findings.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…None of the three studies found that medical severity of MFS were associated to decreased QoL. The largest study found that the patients‐reported symptoms and neurodevelopmental disorders were associated to lower QoL. This study claim that symptoms such as pain, fatigue, psychosocial distress and learning disability may have greater impact on QoL than the objective biomedical findings.…”
Section: Resultsmentioning
confidence: 72%
“…The diagnosis was either self‐reported or not described in the study. Five studies reported only on patients with MFS according to Ghent 1 nosology. Five studies included only patients assessed according to the revised Ghent nosology (Ghent 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations